Fines migration and permeability decline during reservoir depletion coupled with clay swelling due to low-salinity water injection: An analytical study - Suparit Tangparitkul (2020)
© 2020 Elsevier B.V. Fines migration is crucial for reservoir permeability, involving both fine particle detachment and re-deposition along the flow channels. Fines migration behavior can either promote or obstruct fluid flow within the reservoir and is crucial for productivity optimization that needs fundamental understanding. The present work focuses on the contributions from effective stress build-up due to reservoir depletion and decreases in brine salinity from low-salinity water injection. Particle detachment is studied analytically by using the critical retention concentration function modified with stress and salinity dependents. Increase in formation effective stress leads to deformations within the reservoir configurations due to micro-cracks and reduced pore dimensions. Decreased size of the travelling channels promotes particle detachment, while the critical retention concentration decreases. A sensitivity study reveals that, under influence of effective stress, particle size and fluid velocity are dominant parameters controlling the fines migration by influencing the particle detaching forces. With decreasing brine salinity (e.g. via low-salinity water injection), clay particles that are attached on the pore surface increasingly swell, leading to reduction in effective pore space and flow channel. Decreased pore space directly obstructs travelling of suspended particles and fluids which results in permeability decline. Initial clay particle size is found to be a critical factor controlling particle detachment behavior. Small initial particle sizes are not likely to detach from the pore surface as a result of weak detaching forces, hence the analysis finds the critical retention concentration unchanged resulting in negligible permeability decline as a function of brine salinity. Considering both effects, effective stress and brine salinity, stress-dependent effects dominate salinity-dependent effects at low effective stress while the two contribute equally at high effective stress. Permeability decline is also determined from analytical results of the fine particle critical retention concentration, which emphasizes the roles of effective stress and brine salinity on the flow in reservoir porous media.